Pedagogic subject and educational bond in the context of the special school (Praxis Educativa, 2013)
This paper constitutes an essay that sprang from the process of data analysis from different investigations carried out in the context of special schools. Two emergent categories are recaptured: the pedagogic subject and the educational bond, dimensions that merge in a dialectical relation, characterizing the complexity of this educational praxis that acquires different styles depending on the peculiarities of the subjects and of the contextual situations in which it develops. The singular look that the teaching subjects recount as regards their work and, more precisely, their pupils, allows us to understand the importance of these relations, since they construct and mediate the relation of the subject with himself and determine their link with knowledge. The way we feel, see ourselves, behave, eventually how we are, depends on the practices in which we are inserted, where the relationship with others is vital.
Keywords: special school; pedagogic subject; teaching professional practice; singularity; differences